BLE-IOT-PID: Bluetooth Low Energy (BLE) Based IOT Controlled PID Controller for Multi-loop Pilot Plant with Quantum Firefly PSO Optimization - Deshmukh, Jotiram; Tirole, Ritesh; Bhaskar, Anand (International Journal of Sensors Wireless Communications and Control, 2024)
<span class=
Keywords: multi-loop pilot plant